PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTUAN VIDEO ANIMASI TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS III SD - Meisya Rahayu; M. Jaya Adi Putra; Mahmud Alpusari (STKIP Subang, 2026)
This study aims to determine the effectiveness of the Project-Based Learning (PjBL) model assisted by animated videos in IPAS learning on the learning outcomes of third-grade elementary school students. This research employed a quantitative method with a quasi-experimental design. The research subjects consisted of students from classes III A and III B at the selected elementary school, with a total of 35 students. Based on the results obtained from the pre-test and post-test instruments, it was found that the class taught using the Project-Based Learning model assisted by animated videos achieved higher learning outcomes compared to the class that relied solely on textbooks during the learning process. This finding was supported by the results of the Independent Samples Test, which showed a significance value (2-tailed) of < 0.001, indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. Therefore, the implementation of the Project-Based Learning model assisted by animated videos has a significant effect on the IPAS learning result of elementary school students in Phase A.